An advanced methodology for the mix design optimization of hot mix asphalt. (15th May 2016) - Bressi, Sara; Dumont, A.G.; Partl, M.N.
Abstract: The bitumen quantity to add to asphalt mixtures depends on the surfaces of aggregates and filler to be coated. The formulas currently available in the literature have limitations such as considering all the fillers with the same specific surface or the aggregates with spherical or cubical shapes. This paper aims to define an analytical approach for the determination of the optimal dosage of bitumen in HMA proposing new methodologies to go a step further in the resolution of the above mentioned approximations. Indeed, new surface area factors were calculated to determine the aggregates surface considering their real shapes and volumes. Afterwards, the authors proposed a detailed characterization of two types of fillers and the critical filler concentration, introduced by Faheem and Bahia, was used to calculate the minimum amount of bitumen for maintaining the mastic in a diluted state and filling the voids in the mixtures. Finally, a verification of the formula developed was carried out with specific laboratory tests. These results allow the challenge of revising the method of calculating the specific surface of the aggregates and filler to be addressed with the final goal to include them in a new mix design optimization for HMA. Graphical abstract: Highlights: Introduction of the concept of critical filler concentration in the mix design of hot mix asphalt A new methodology for the mix design optimization of asphalt mixtures was developed. Key roles in the mix design have been assigned to the filler properties and new surface area factors for aggregates. The estimation of the optimal bitumen quantity allows reducing laboratory testing efforts.